PERANAN SEKTOR PERTANIAN DALAM PEMBANGUNAN WILAYAH KOTA TOMOHON - Jessi S. Tampun; Gene H.M. Kapantow; Grace A.J. Rumagit; Lorraine W.Th. Sondakh (COCOS, 2015)
ABSTRACTJessi S. Tampun , 2014. Role of Agriculture in Regional Development Tomohon ( under the guidance of G.H.M. Kapantow , as Chairman of the Advisory Committee , as well as Grace A.J. Rumagit and Lorraine W.Th. Sondakh as Members ) .This study aims to determine the contribution of the agricultural sector to regional development in Tomohon , knowing the position of the agricultural sector and sub- sector of food crops , plantations , livestock , forestry , and fisheries in Tomohon and determine the role of agriculture in the economy in Tomohon seen from the figures given income multiplier .The research was conducted in Tomohon with data collection at the Central Bureau of Statistics Tomohon and North Sulawesi . Data were analyzed by using several types of calculations includingcalculating contributions , LQ and DLQ analysis to identify the agricultural sector as well as changes in the position and income multiplier analysis to look at the role of the agricultural sector The results of research show In 2013 the agricultural sector has contributed 14 , 45 % of the total GDP Tomohon with two sub-sectors of the agricultural sector which has the greatest contribution is the food crops subsector which contributed 5.40% to the total GDP . The position of the agricultural sector that is non- base in 2013 , a period to akang come into a position change by sub- sector base that follows the sub- sectors of the food crops , livestock and forestry . Plantation and fisheries sub- sectors remain at non- base . The role of the agricultural sector in terms of revenue in Tomohon affect change in the total income of the area in Tomohon . The advice in this experiment is a need for special attention to the agricultural sector in Tomohon remember in future agricultural sector will experience a change in position and supported through Tomohon known as the City of Agro .Keywords: contribution, agricultural sector, regional development.